Dynamic glucose enhanced MRI of the placenta in a mouse model of intrauterine inflammation. (September 2018) - Wu, Dan; Xu, Jiadi; Lei, Jun; Mclane, Michael; van Zijl, Peter C.; Burd, Irina
Abstract: Introduction: We investigated the feasibility of dynamic glucose enhanced (DGE) MRI in accessing placental function in a mouse model of intrauterine inflammatory injury (IUI). DGE uses the glucose chemical exchange saturation transfer (glucoCEST) effect to reflect infusedd -glucose. Methods: IUI was induced in pregnant CD1 mice by intrauterine injection of lipopolysaccharide (LPS) on embryonic day 17. In vivo MRI was performed on an 11.7 T scanner at 6 h s after injury, and glucoCEST effect was measured using an on-resonance variable delay multi-pulse (onVDMP) technique. onVDMP acquisition was repeated over a period of 25 min, andd -glucose was infused 5 min after the start. The time-resolved glucoCEST signals were characterized using the normalized signal difference ( Δ S N ) between onVDMP-labeled and nonlabeled images. Results: Δ S N in the PBS-exposed placentae (n = 6) showed an initial drop between 1 and 3 min after infusion, followed by a positive peak between 5 and 20 min, the time period expected to be associated with the process of glucose uptake and transport. In the LPS-exposed placentae (n = 10), the positive peak was reduced or even absent, and the corresponding area-under-the-curve (AUC) was significantly lower than that in the controls. Particularly, the AUC maps suggested prominent group differences in the fetal side of the placenta. We also found that glucose transporter 1 in the LPS-exposed placentae did not respond to maternal glucose challenge. Discussion: DGE-MRI is useful for evaluating placental functions related to glucose utilization. The technique uses a non-toxic biodegradable agent (d -glucose) and thus has a potential for rapid translation to human studies of placental disorders. Highlights: Feasibility of glucoCEST to access placental function was examined in a mouse model. GlucoCEST effect was obtained with an on-resonance variable delay multi-pulse method. Time-resolved glucoCEST effect increased after glucose infusion in normal placenta. Placental glucoCEST effect reduced acutely after intrauterine inflammation. Glucose transporter 1 did not respond to glucose infusion in the injured placentae.